THE IMAGE OF THE SPY IN THE NOVEL BY S. POSTOLOVSKYI «THE ENEMY, OR THE GOD’S WRATH » – A HERO OR A CRIMINAL? - Zemlianska, A. V.; Zemlianskyi, A. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article is devoted to the analysis of images of the main characters of the spy in S. Postolovskyi’s novel «The Enemy, or the Wrath of God». It is emphasised on author’s traditional representations of the typical image of spy showed in the images of James Bond (by I. Fleming), George Smiley (by J. Le Carre) and Stierlitz (by Yu. Semenov). The author updates these images according to the realities of the present. It is determined that the participants of the operation «The God’s Wrath», depicted in the S. Postolovskyi’s novel, are very colorful figures, people that are ready to fight, but this desire to take revenge on the enemies of their country is based for each of them on personal reasons: the desire to get a higher post, to find out the truth about the work of the spy-saboteur and to determine their own place in the battle for their country, establish justice, and so on. The writer successfully combines the contradictory features of heroes and criminals in their characters, emphasizing their ambiguity, which makes them believable, living people, and not ideologically well-established figures. It was found out that the most ideologized image in the work is the figure of Captain Ivan Principle, the favorite S. Postolovskyi’s hero, who has already met in the previous writer’s works. The surname of this character is fully matched with his inner qualities: he is honest, fair, takes the attention of women, and in his actions he is always guided by the law and believes that the means do not always justify the goal. The author tried to bring out a new image of a spy, a modern hero who could become a sample for the young generation. It was also revealed that in the images of other ministers of the Office, who participated in the organization of Operation «The God’s Wrath», – General Bulldog, Colonel Myron and Captain Nechypailo – the writer depicted the typical representatives of his time, capable of high aspirations and courageous deeds, but at the same time they are typical executors of any order, often criminal, when it coincides with their notions of justice and duty. Thus, S. Postolovskyi presented his own vision of Ukraine’s fate in the «hybrid war» with Russia and those people whom the result of this war directly depends on. Since he can’t foresee the future, the author leaves his protagonists a tragic fate, just like life itself.